Cornbread Nation 7 : The Best of Southern Food Writing - Lam, Francis (Book collections on Project MUSE., 2014)
How does Southern food look from the outside? The form is caught in constantly dueling stereotypes: It's so often imagined as either the touchingly down-home feast or the heartstopping health scourge of a nation. But as any Southern transplant will tell you once they've spent time in the region, Southerners share their lives in food, with a complex mix of stories of belonging and not belonging and of traditions that form identities of many kinds. Cornbread Nation 7, edited by Francis Lam, brings together the best Southern food writing from recent years, including well-known food writers such as Sara Roahen and Brett Anderson, a couple of classic writers such as Langston Hughes, and some newcomers. The collection, divided into five sections ("Come In and Stay Awhile," "Provisions and Providers," "Five Ways of Looking at Southern Food," "The South, Stepping Out," and "Southerners Going Home"), tells the stories both of Southerners as they move through the world and of those who ended up in the South. It explores from where and from whom food comes, and it looks at what food means to culture and how it relates to home.